Ethnic-specific association of amylase gene copy number with adiposity traits in a large Middle Eastern biobank - Niccolo’ Rossi (Nature Portfolio, 2021)
Abstract Studies assessing the impact of amylase genes copy number (CN) on adiposity report conflicting findings in different global populations, likely reflecting the impact of ancestral and ethnic-specific environment and lifestyle on selection at the amylase loci. Here, we leverage population size and detailed adiposity measures from a large population biobank to resolve confounding effects and determine the relationship between salivary (AMY1) and pancreatic (AMY2A) amylase genes CN and adiposity in 2935 Qatari individuals who underwent whole-genome sequencing (WGS) as part of the Qatar Genome Programme. We observe a negative association between AMY1 CNs and trunk fat percentage in the Qatari population (P = 7.50 × 10−3) and show that Qataris of Arab descent have significantly lower CN at AMY1 (P = 1.32 × 10−10) as well as less favorable adiposity and metabolic profiles (P < 1.34 × 10−8) than Qataris with Persian ancestry. Indeed, lower AMY1 CN was associated with increased total and trunk fat percentages in Arabs (P < 4.60 × 10−3) but not in Persians. Notably, overweight and obese Persians reported a significant trend towards dietary restraint following weight gain compared to Arabs (P = 4.29 × 10−5), with AMY1 CN showing negative association with dietary self-restraint (P = 3.22 × 10−3). This study reports an association between amylase gene CN and adiposity traits in a large Middle Eastern population. Importantly, we leverage rich biobank data to demonstrate that the strength of this association varies with ethnicity, and may be influenced by population-specific behaviors that also contribute to adiposity traits.